Risk analysis of complex systems: using hierarchical bayesian models - Yan, Zhenyu (Henry Stewart Talks, 2012)
Risk analysis, Risk assessment, Risk management, Likelihood, Consequence, Sparse data, Systems engineering, Bayesian statistics, Hierarchical Bayesian model, Cyber attack, Extreme event, Rare event, Process control system, Markov Chain Monte Carlo (MCMC) simulation, Winbugs